Uma experiência de consultas com palavras-chave em fontes de dados heterogêneas na web - Filgueiras, Alison Carlos (2013)
Context: keyword research is a highly used feature for retrieval of information through the search engines available on the Internet. Much of the information in the world, however, is not achieved by conventional search to be stored in databases, relational most. The integrated search information from di erent data sources is explored by several studies, still, no studies were found to bring e ective solutions when it includes, among these data sources, relational databases. Objective: The emphasis of this study is to present a solution for retrieval of information stored in heterogeneous data sources using the OAI-PMH as a mechanism to enable interoperability. Method: Implementing a system that runs queries for keywords in heterogeneous data sources from the collection of metadata exposed to OAIPMH data providers in. Furthermore, the proposal is for a web service that uses public methods to allow information relational databases are returned without the need for additional e orts, such as knowledge of the structure of the database or use SQL. Results: The simulations produced a return of information from metadata of digital objects and relational databases, obtained from data providers. The query execution examples was successful in retrieving information on all data sources surveyed. Conclusion: This work proposes a solution for information retrieval stored in heterogeneous data sources. The proposed solution was feasible to allow consultation by keywords in digital libraries and relational databases using the OAI-PMH. The proposed web service enabled information relational databases were obtained by external applications, without requiring